PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KINERJA USAHA INDUSTRI KECIL DAN MENENGAH DI PURWOKERTO UTARA - Purwidianti, Wida; Rahayu, Tri Septin Muji (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
AbstractThe purpose of this study is to test the internal and external factors that have an influence on theperformance of small and medium-sized industrial enterprises. The first hypothesis, which states that internalfactors have a positive impact on business performance is not fully supported. This is because of the threevariables that are internal factors; only one variable is a business strategy that has a significant positive effect.Meanwhile, two other variables, namely the value of entrepreneurship and technical aspects and operation haveno significant effect.The second hypothesis states that external factors have a positive impact on business performancewhich is also not supported. It can be seen from the results of statistical tests that found no evidence thataspect of the economy, government policy aspects, and aspects related to the role of institutions do not have asignificant impact on business performance.Keywords: internal factors, external factors, business performance, small business enterprise